PERBANDINGAN EFEKTIVITAS EKSTRAK ETANOL DAUN KEMANGI DENGAN BAWANG PUTIH TERHADAP PERTUMBUHAN BAKTERI STAPHYLOCOCCUS AUREUS - Marcelino, Nico; Clara, Elisabeth Chindy; Fauhan, Kania Indryani; Ramadhana, Alfi Syahri; Lister, I Nyoman Echrich (Universitas Jambi, 2020)
Writing the results of the study was conducted to assess the effectiveness comparison of the ethanol extract of basil leaves with garlic with a concentration of 5%, 10%, 15% of each extract against the growing power of the Staphylococcus aureus bacteria. Staphylococcus aureus bacteria are gram-positive, cocci-shaped bacteria that live in colonies. These bacteria are normal flora in the human body that can harm humans. This study uses an experimental method with a post-test only design and the sample collection uses purposive sampling. The effectiveness test was carried out using the disk diffusion method, where the paper disc would be moistened with basil leaves ethanol extract of each concentration, is 5%, 10%, 15% and so was the ethanol extract of garlic. The results of the data obtained from this study continued with the Oneway-Anova test which will be continued with the Post-Hoc test, wherein the test there were significant differences from each treatment given. In bacteria treated with ethanol extract 15% basil leaves against Staphylococcus bacteria aureus, the effectiveness of the inhibition zone was found to be 9.2 mm in diameter where the inhibition zone was below the ethanol extract of 15% garlic which was 22.8 mm. Ethanol extract of 15% garlic has a good antimicrobial effect compared with ethanol extract of basil leaves 15% against Staphylococcus aureus bacteria.